Physicochemical and mechanical degradation of polyamide 11 induced by hydrolysis and thermal aging. Issue 23 (23rd February 2019) - Maïza, S.; Lefebvre, X.; Brusselle‐Dupend, N.; Klopffer, M.‐H.; Cangémi, L.; Castagnet, S.; Grandidier, J.‐C.
ABSTRACT: This article deals with the effect of both temperature and water activity on polyamide 11 physicochemical and mechanical properties. The purpose of this work is to describe the ductile–brittle transition of polyamides during aging in a wet environment using a mechanical behavior model. For that it is necessary to make physicochemical analyzes (DSC, FTIR, GPC, viscosity) and mechanical tests (uniaxial tensile test and dynamic mechanical thermal analysis). All of these tests were performed on unaged samples and on aged samples for until 60 days. Two types of aging conditions were performed: In water in an acidic medium at temperature, and in purely thermal conditions in a neutral environment. Changes in mechanical properties with aging were observed in the polymer and were correlated to morphological changes deduced from the physicochemical characterizations. An increase of the second yield stress related to the recrystallization and a decrease of the strain at break due to the decrease of the molecular weight were observed during aging. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47628. Abstract :